2017
DOI: 10.1111/acel.12569
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between soluble guanylate cyclase signaling and neuropeptides extends lifespan in the nematodeCaenorhabditis elegans

Abstract: SummaryOxygen (O2) homeostasis is important for all aerobic animals. However, the manner by which O2 sensing and homeostasis contribute to lifespan regulation is poorly understood. Here, we use the nematode Caenorhabditis elegans to address this question. We demonstrate that a loss‐of‐function mutation in the neuropeptide receptor gene npr‐1 and a deletion mutation in the atypical soluble guanylate cyclase gcy‐35 O2 sensor interact synergistically to extend worm lifespan. The function of npr‐1 and gcy‐35 in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
(64 reference statements)
0
15
0
Order By: Relevance
“…It has been previously shown that both E. coli HT115 and OP50 differentially modulate the metabolism, behavior, development and aging of worms [ 53 ] up to an extent that certain genes may have opposite effects on the lifespan of worms fed on OP50 and HT115 [ 54 - 56 ]. Similarly, the use of UV-killed bacteria may differentially affect the lifespan of certain mutants [ 57 ]. Most of the previously published hif-1 (ia4) worm lifespan experiments have been performed on UV-killed OP50 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that both E. coli HT115 and OP50 differentially modulate the metabolism, behavior, development and aging of worms [ 53 ] up to an extent that certain genes may have opposite effects on the lifespan of worms fed on OP50 and HT115 [ 54 - 56 ]. Similarly, the use of UV-killed bacteria may differentially affect the lifespan of certain mutants [ 57 ]. Most of the previously published hif-1 (ia4) worm lifespan experiments have been performed on UV-killed OP50 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unc-9 is expressed in glutamatergic sensory neurons that respond to chemical, temperature and oxygen cues which are known to influence lifespan. However, these neurons do so by regulating daf-16 FOXO signalling 51,54,83 . Our data show that unc-9 acts independently of daf-16 to regulate longevity, making it unlikely that unc-9 regulates lifespan in these neurons.…”
Section: Discussionmentioning
confidence: 99%
“…These neuron classes show intriguing shared features: they are dominated by sensory neurons -19 of the 31 classes are sensory neurons. Sensory perception plays a central role in regulating C. elegans lifespan 49,50 , and chemosensory 51 , thermosensory 52,53 and oxygensensing neurons 54,55 have been shown to shorten or extend the animals' lifespan in an environmental context-dependent manner. The oxygen-sensing neurons AQR and PQR signal tonically at 21% ambient oxygen but are largely inactive at reduced O2 levels (7%) 56 .…”
Section: The Glutamatergic Unc-9-expressing Neurons Are Predominantlymentioning
confidence: 99%
“…The lifespan of npr-1(−) worms was slightly, but significantly, longer than that of N2 animals bearing the npr-1(215V) allele [ 4 ]. This result fitted our prediction that the aggregation behaviour can create a “healthier O 2 microenvironment” and thus increases the lifespan of npr-1(−) worms.…”
mentioning
confidence: 99%
“…However, the result was the opposite. The lifespan of gcy-35(−);npr-1(−) worms was profoundly longer than that of both N2 and npr-1(−) worms [ 4 ]. In fact, the joint effect of gcy-35(−) and npr-1(−) on worm lifespan is synergistic, since gcy-35(−) worm lifespan was similar to N2 and npr-1(−) by itself elicits only a small increase in lifespan.…”
mentioning
confidence: 99%